A Valid and Reliable Scale for Developing Programming-Oriented Computational Thinking - Kılıç, Servet; Gökoğlu, Seyfullah; Öztürk, Mücahit (SAGE Publications, 2020)
In this research, a scale was developed to determine the programming-oriented computational thinking skills of university students. The participants were 360 students studying in various departments at different universities in Turkey for computer programming. The scale consists of 33 items under conceptual knowledge, algorithmic thinking, and evaluation subscale. While there was no significant difference between the students’ conceptual knowledge and algorithmic thinking skills, the evaluation skills of male students differed significantly compared to females. Programming experience has a significant effect on conceptual knowledge, algorithmic thinking, and evaluation. The algorithmic thinking skills of the students who have low, middle, and high-level programming experience differed significantly. In terms of the development of conceptual knowledge and evaluation skills, it was observed that students should have at least one year of programming experience, but this experience will not make a significant difference if it is four years or more. It is thought that this scale, which is structured for different applications (e.g., web, game, robot) and learning environments (e.g., text, block) within the framework of its programming capabilities (conceptual, semantic, strategic knowledge), will contribute significantly to the evaluation of computational thinking as programming oriented.
Keywords: Computational Thinking; CTS Scale Development; Computer Programming and Programming Language; Algorithmic Thinking; Evaluation; Conceptual Knowledge; 4. Education